Arahan Optimasi Penggunaan Lahan Melalui Pendekatan Telapak Ekologis di Kabupaten Gresik - Achmad Ghozali; Putu Gde Ariastita (Jurnal Wilayah dan Lingkungan, 2013)
Environmental capacity in Gresik Regency is imbalance condition in accommodating every increase of activity due to population growth and intensive land use change. It is marked by the disproportion between environmental capacity and nature resource consumption where the land use change in Gresik Regency gave impact to ecological damage such as land productivity degradation, water scarcity, flood, and environmental pollution. This research aims to determine the carrying capacity components in the optimization of land use in Gresik Regency. The method used is through ecological footprint approach that can be used to measure nature resource consumption rate and land capability in providing that needs in global hectare land (gha) unit. The result of this research showed that Gresik biocapacity reached 319.179,6 gha that is widely spread in the peri-urban area. The highest biocapacity percentage is on agricultural land with 53,92%. However, that biocapacity is not comparable to the ecological footprint consumption that reached 1,63 million gha especially in urban area due to the high population and activity intensity. This worsen the imbalance of carrying capacity in Gresik Regency that has been already experienced ecological deficit for 1,04 gha/capita. Every land types is experiencing deficit condition and only ranch farm land that has surplus of 0,05 gha/capita. The mapping result showed that land use optimization is needed by implementing compact city development so that it can be easier to control and create energy use efficiency. Besides of that, agropolitan system implementation is needed to increase land productivity in peri-urban area as major resources in Gresik Regency.